PENGARUH LATIHAN KELINCAHAN DAN LATIHAN KECEPATAN TERHADAP PENINGKATAN KEMAMPUAN DRIBBLING DALAM PERMAINAN SEPAKBOLA PADA SISWA ESKTRAKURIKULER SMP NEGERI 1 EREMERASA KABUPATAEN BANTAENG - Andi zulfiansyah mappamadeng; Irvan; Juhanis; Muhammad Kamal; Muh. Adnan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of agility and speed training on dribbling skills in extracurricular soccer students at SMP Negeri 1 Eremerasa, and to compare the effectiveness of both forms of training. This study used an experimental method with a Two Groups Pretest-Posttest Design. The results showed that both agility and speed training had a significant effect on improving dribbling skills